LOOKING FOR ALTERNATIVE ONLINE PROMOTION STRATEGY IN VIRTUAL STORE BALERINA BEAUTY SHOP: AN APPLICATION OF ANALYTIC HIERARCHY PROCESS - Fatimah Abdillah (SAMPURASUN, 2019)
Technology through the internet changes human lifestyle and culture. Ease access to the internet is major support for developing the e-commerce industry. However, in some online companies, not only the internet but also other supporting factors are needed to grow, such as alternative marketing strategies. In the case of Balerina beauty shop, the decreasing number of its visitors for months became the main concern. The company chooses promotional focus as the strategy to deal with visitor problems. Previous research in e-business and analytical hierarchy processes (AHP) issues have not been a concern to promotion strategy, so this study aims to explore the application of analytical hierarchy processes (AHP) in virtual stores and find elements that support online promotion strategies. This study uses a qualitative and quantitative approach. The results of the study indicate that the company has implemented an online promotion strategy such as web promotion with the CPC system, price discounts, social networking systems, smartphone applications, and online group discussions. Actors who play a main role in the company when making strategic decisions are directors, marketing managers, and IT departments. The marketing strategy of the company purposes to increase sales, consumers' awareness, competition, and information dissemination. AHP results show that alternative strategies for the progress of the company, based on priority ranking, are markets, search engine optimization, web advertising, and direct mail. For further development in performance, giving priority to the development of IT skills can be applied.